Googling on Colonoscopy: A Retrospective Analysis of Search Engine Statistics - Kaminski, Mikolaj (Clin Exp Gastroenterol, 2020)
PURPOSE: Colonoscopy is a gold standard for screening and diagnosis of colorectal cancer (CRC). The data from the search engine may reveal what information on coloscopy gains the attention of Internet users. We aimed to investigate Google searches trends and terms related to colonoscopy. PATIENTS AND METHODS: We retrieved statistics searches related to colonoscopy using Google Trends (GT) and Google Ads (GA) for the period from April 2016 to March 2020. The GT data was used for the analysis of time and regional search patterns worldwide. GA data for Australia, Canada, Ireland, New Zealand (NZ), Poland, the United Kingdom (UK), and the United States (US) were used to calculate the search volume of categories of queries related to colonoscopy. RESULTS: Globally, the relative search volume on colonoscopy has increased until the COVID-19 outbreak and revealed seasonal variation: the highest interest was observed in March (CRC awareness month), and the lowest during December (Christmas holidays). The highest number of searches per 1000 Google users-years was done in Poland (59.62) and the lowest in the UK (19.46). Most commonly, Google users searched for details on colonoscopy techniques (Australia, Canada, Ireland, NZ), anesthesia during the procedure (Poland), facility performing colonoscopy (UK, US). In all seven countries, less than 2% of queries concerned with bowel preparation before the procedure. CONCLUSION: Before the COVID-19 pandemic, the interest in colonoscopy has increased among Google users. Google users may underestimate the importance of proper bowel preparation.